2008
DOI: 10.1107/s0909049508031853
|View full text |Cite
|
Sign up to set email alerts
|

X-ray fluorescent CT imaging of cerebral uptake of stable-iodine perfusion agent iodoamphetamine analog IMP in mice

Abstract: Using X-ray fluorescent computed tomography (XFCT), the in vivo and ex vivo cerebral distribution of a stable-iodine-labeled cerebral perfusion agent, iodoamphetamine analog (127I-IMP), has been recorded in the brains of mice. In vivo cerebral perfusion in the cortex, hippocampus and thalamus was depicted at 0.5 mm in-plane spatial resolution. Ex vivo XFCT images at 0.25 mm in-plane spatial resolution allowed the visualisation of the detailed structures of these regions. The quality of the XFCT image of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Simionovici et al demonstrated high-resolution X-ray fluorescence micro-tomography in 2000 [4]. In 2008, Takeda et al performed in vivo XFCT imaging of iodine perfusion in a mouse brain [5]. All of these experiments used mono-energetic X-rays from synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Simionovici et al demonstrated high-resolution X-ray fluorescence micro-tomography in 2000 [4]. In 2008, Takeda et al performed in vivo XFCT imaging of iodine perfusion in a mouse brain [5]. All of these experiments used mono-energetic X-rays from synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Small beam size and fine scanning steps result in high spatial resolution down to 150 mm, with the expense of long imaging times. For example, the 20 mgAu ml 21 concentration measured with a single collimated detector by Manohar et al 5 required an imaging time of more than 8 h. Long imaging times are impractical for pre-clinical imaging, as duration of animal anaesthesia should not exceed 1.5 h. Takeda et al 6 were able to generate synchrotron pencil beam K-shell XFCT images of iodine in mice brains with imaging times of 1.5 h.…”
Section: Imaging Timementioning
confidence: 99%
“…FXCT has been a vital tool in both material and biomedical sciences [4][5][6]. Molecular imaging using a non-radioactive imaging-agent, such as iodine, is also of potential use in medicine and pharmacology, where the visualization of various disease processes in small animals is used to investigate the cause, diagnosis and therapy of diseases from the characteristics and behavior of imaging agents in the subject.…”
Section: Introductionmentioning
confidence: 99%